Acid ceramidase regulates CD8+ T-cell exhaustion via type I interferon-mediated upregulation of PD-L1 - Hu, Zhongwen; Abdelrahman, Hossam; Elwy, Abdelrahman; Kuang, Fei; Dhiman, Swati; Ali, Shafaqat; Marson, Marcel; Holnsteiner, Lisa; Hamdan, Thamer A.; Friebus-Kardash, Justa; Wiebeck, Elisa; Hansen, Wiebke; et al. (Frontiers in Immunology, 2025)
Besides its robust antiviral activity, type I interferon (IFN-I) also exerts immunomodulatory effects and can even drive pathology during chronic viral infections. Mechanisms that regulate IFN-I induction during virus infection, thus strongly affecting the outcome of disease, remain to be defined. Here, using the lymphocytic choriomeningitis virus (LCMV) Docile strain, we identified acid ceramidase (aCDase, Asah1) as a critical lipid-metabolic regulator of endosomal, nucleic acid-driven IFN-I responses and disease outcome during chronic virus infection. aCDase is highly expressed in plasmacytoid dendritic cells (pDCs) and required for robust early IFN-I production. aCDase deficiency resulted in ceramide accumulation, blunting IFN-α/β induction, impairing IFN-I-dependent upregulation of programmed death-ligand 1 (PD-L1) on antigen-presenting cells and preventing the exhaustion of virus-specific CD8+ T cells, leading to severe immunopathology. This pathology is abrogated by CD8+ T-cell depletion or by adoptive transfer of IFN-I-induced PD-L1-expressing macrophages. Conversely, limiting ceramide production in acid sphingomyelinase (Asm)-deficient mice prevented ceramide accumulation, and pDCs showed accelerated IFN-I induction. Mechanistically, ceramide abundance regulated IFN-I production by altering endosomal signaling microdomains. Collectively, our findings reveal ceramide homeostasis as a key determinant of IFN-I-driven CD8+ T-cell exhaustion and immunopathology during chronic viral infection and highlight aCDase as a potential therapeutic target.